Evaluation of the optimal positioning of subcutaneous butterfly when administering injectable opioids in cancer patients - MITREA, NICOLETA (Clujul Med, 2016)
BACKGROUND AND AIMS: The increasing number of cancer patients, together with the development of new palliative care services in Romania, warrants the evaluation of nursing strategies meant to improve the level of comfort of patients who are suffering from advanced cancer. The main objective of the study was to evaluate the optimal positioning of the subcutaneous (sc) butterfly, in accordance with its resistance in the insertion tissue, the local complications that may occur, and the evaluation of the time of resistance at the insertion site (puncture) with the daily frequency of injectable opioid administration. METHODS: A prospective experimental pilot study was designed and conducted between January and May 2011. Patients admitted to the Hospice Casa Sperantei (Brasov, Romania) with moderate or severe cancer pain, who were receiving subcutaneously opioids, over the age of 18, with normal body index ranging from 18.5 – 22.0, were assigned randomly to one of two groups, after signing the informed consent. In group one, the butterfly was positioned with the needle bevel up – this was considered to be the control group as this modality of inserting the needle is considered standard practice; in group two the butterfly was positioned with the needle bevel down – experimental group. The drugs used for pain relief were sc tramadol for moderate pain and sc morphine for severe pain. RESULTS: Our research supported the hypothesis that the occurrence of local complications coincides with the decrease of sc butterfly resistance in time at the place of insertion, and the sc butterfly has a higher rate of resistance in time at the insertion site if the frequency of injectable opioids administration is lower (twice per day). CONCLUSION: The positioning of the butterflies with the bevel down (experimental group) is associated with a longer resistance in time at the site of insertion, and causes fewer local complications compared to the sc butterflies positioned with the bevel up (control group).